A Photoredox Catalysis Approach for the Synthesis of Both the ABDE and the ABCD Cores of Tronocarpine - Contreras-Cruz, David A.; Castañón-García, Mario; Becerril-Rodríguez, Enrique; Miranda, Luis D. (Synthesis, 2020)
A general strategy for the facile construction of both the ABDE and ABCD cores of tronocarpine, chippiine and dippinine alkaloids through the retrosynthetic disconnection of the polycyclic motifs into an indole or tryptamine fragment and a suitably functionalized alkyl chain is presented. The approach is enabled by an efficient Ir(III)-catalyzed, photoredox-mediated radical addition of tetramethyl 1-bromopentane-1,1,3,5-tetracarboxylate and dimethyl 2-bromopentanedioate selectively at C-2 of the indole. Subsequent intramolecular cyclization events furnish the desired ABDE and ABCD polycyclic cores in good preparative yields.
Keywords: indoles; alkaloids; radicals; photoredox catalysis; tronocarpine